Kinerja Pegawai Perbankan di Era Digital: Peran Teknologi Inovasi dan Tantangan Beban Kerja Berlebih - Anjani, Alvina; Hakim, Lukman Nul; Yohanson, AK (Lembaga Penelitian, dan Pengabdian Kepada Masyarakat (LPPM) STIE GENTIARAS Bandar Lampung dan berkolaborasi dengan Ikatan Akuntan Indonesia Kompartemen Akuntan Pendidik (IAI KAPd), 2025)
Digital transformation in the banking sector has created new challenges in managing employee performance, especially related to technology adoption and workload management. This study aims to evaluate the effect of innovation technology and workload towards employee performance at Bank BRI Pringsewu, considering the lack of simultaneous studies on this issue in the context of regional banks. A quantitative method was used with a survey to the entire employee population (38 respondents). Data were analyzed using multiple linear regression. The result shows that the implementation of innovation technology contributed positively and significantly to employee performance, while excessive workload had a negative and significant effect. This study emphasizes the importance of continuous technology training and realistic workload management to support productivity. Practical implications are directed at increasing operational efficiency through a combination of digital strategies and balanced HR management.